2000
DOI: 10.1021/jo005661t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functionalization of meso-Aryl-Substituted Corroles

Abstract: The Rothemund condensation reaction of pyrrole and aldehydes is an extensively used route to meso-tetraarylporphyrins, but simple modifications of the reaction conditions allow the formation of different macrocycles other than the expected porphyrin. In the presence of an excess of pyrrole, this modified Rothemund approach leads to the synthesis of meso-triary-substituted corroles. This methodology allows the preparation of a wide range of substituted corroles starting from commercially available products. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(168 citation statements)
references
References 16 publications
5
158
0
3
Order By: Relevance
“…All reactive substrates for LFP kinetic studies and catalytic competitive oxidations were the best available purity (Aldrich) and were passed through a dry column of active alumina (Grade I) before use. Corrole ligands employed in this study, H 3 TPFC, [3] H 3 TPC, [13] and H 3 BPMFC, [14] were prepared according to the literature procedures, and their characterization data ( 1 H NMR, UV/Vis and HRMS-ESI) were consistent with reported values.…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…All reactive substrates for LFP kinetic studies and catalytic competitive oxidations were the best available purity (Aldrich) and were passed through a dry column of active alumina (Grade I) before use. Corrole ligands employed in this study, H 3 TPFC, [3] H 3 TPC, [13] and H 3 BPMFC, [14] were prepared according to the literature procedures, and their characterization data ( 1 H NMR, UV/Vis and HRMS-ESI) were consistent with reported values.…”
Section: Methodsmentioning
confidence: 64%
“…The 5,15-bis(pentafluorophenyl)-10-(p-methoxyphenyl)corrole system (b) is abbreviated (H 3 BPFMC). Each of the corrole ligands was known, [3,13,14] as were the manganese(iii) complexes 1 a [5] and 1 c, [15] but the manganese derivative 1 b is new.…”
Section: Resultsmentioning
confidence: 99%
“…Corroles have received a great deal of attention in recent years (10)(11)(12)(13), owing to dramatic advances in methods for their preparation (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Of interest here is a gallium(III) complex, 1 [Ga(tpfc)] (32)(33)(34)(35), where tpfc represents the trianion of 5,10,15-tris(pentafluorophenyl)corrole [H 3 (tpfc)].…”
mentioning
confidence: 99%
“…[83,84] As early as 1996, Rose et al [85] reported the isolation of meso-tris(4-tert-butyl-2,6-dinitrophenyl)corrole as a minor by-product of a classical porphyrin synthesis, but the significance of this finding went almost unnoticed. The situation changed in 1999 with reports by Gross et al [86,87] and Paolesse et al [88,89] of one-pot corrole syntheses-initially still serendipitous-involving pyrrole-aldehyde condensations.…”
Section: One-pot Corrole Synthesesmentioning
confidence: 99%